A qualitative exploration of the role of primary care in supporting colorectal cancer patients. - Hall, S; Gray, N; Browne, S; Ziebland, S; Campbell, N (2012)
PURPOSE: To explore experiences and support needs of people with colorectal cancer, with a focus on identifying opportunities for primary care interventions. METHODS: We conducted a new qualitative analysis of an existing dataset, comprising semi-structured interview transcripts from 39 people with colorectal cancer from across the UK, interviewed in 2001-2002 for www.healthtalkonline.org . Then, we conducted semi-structured interviews with 30 people with colorectal cancer from North East Scotland and Glasgow in 2009 and analysed these new data to explore themes and challenge hypotheses that emerged from the Healthtalkonline data. RESULTS: Formal sources of support, including that from primary care, were valued by those who received them, but provision was described as sporadic both in 2002 and in 2009. However, more of the 2009 participants gave descriptions of specialist nurse and community nurse involvement, and telephone contact from general practitioners, which were welcomed. Improvements in meeting information needs, particularly on the issues of diet and sex, were identified by 2009. A recurring issue reported by patients was the distress experienced by their own friends and family; some patients found themselves having to provide, rather than receive, emotional support at this difficult time. CONCLUSIONS: There have been improvements in support for people with colorectal cancer since 2002, with more specialist and community nurse involvement, and telephone contact from general practitioners, but provision remains piecemeal. Patients would benefit if their families received support, and primary care may be in a good position to provide this. A proactive approach from general practitioners in the post-discharge period is valued.